Sodium Thiosulfate Improves Intestinal and Hepatic Microcirculation Without Affecting Mitochondrial Function in Experimental Sepsis - Schulz, Jan; Kramer, Sandra; Kanatli, Yasin; Kuebart, Anne; Bauer, Inge; Picker, Olaf; Vollmer, Christian; Truse, Richard; Herminghaus, Anna (Frontiers in Immunology, 2021)
Introduction: In the immunology of sepsis microcirculatory and mitochondrial dysfunction in the gastrointestinal system are important contributors to mortality. Hydrogen sulfide (H2S) optimizes gastrointestinal oxygen supply and mitochondrial respiration predominantly via K(ATP)-channels. We tested the hypothesis that sodium thiosulfate (STS), an inducer of endogenous H2S, improves intestinal and hepatic microcirculation and mitochondrial function via K(ATP)-channels in sepsis. Methods: In 40 male Wistar rats colon ascendens stent peritonitis (CASP) surgery was performed to establish sepsis. Animals were randomized into 4 groups (1: STS 1 g • kg-1 i.p., 2: glibenclamide (GL) 5 mg • kg-1 i.p., 3: STS + GL, 4: vehicle (VE) i.p.). Treatment was given directly after CASP-surgery and 24 hours later. Microcirculatory oxygenation (µHBO2) and flow (µflow) of the colon and the liver were continuously recorded over 90 min using tissue reflectance spectrophotometry. Mitochondrial oxygen consumption in tissue homogenates was determined with respirometry. Statistic: two-way ANOVA + Dunnett´s and Tukey post - hoc test (microcirculation) and Kruskal-Wallis test + Dunn’s multiple comparison test (mitochondria). p < 0.05 was considered significant. Results: STS increased µHbO2 (colon: 90 min: + 10.4 ± 18.3%; liver: 90 min: + 5.8 ± 9.1 %; p < 0.05 vs. baseline). Furthermore, STS ameliorated µflow (colon: 60 min: + 51.9 ± 71.1 aU; liver: 90 min: + 22.5 ± 20.0 aU; p < 0.05 vs. baseline). In both organs, µHbO2 and µflow were significantly higher after STS compared to VE. The combination of STS and GL increased colonic µHbO2 and µflow (µHbO2 90 min: + 8.7 ± 11.5 %; µflow: 90 min: + 41.8 ± 63.3 aU; p < 0.05 vs. baseline), with significantly higher values compared to VE. Liver µHbO2 and µflow did not change after STS and GL. GL alone did not change colonic or hepatic µHbO2 or µflow. Mitochondrial oxygen consumption and macrohemodynamic remained unaltered. Conclusion: The beneficial effect of STS on intestinal and hepatic microcirculatory oxygenation in sepsis seems to be mediated by an increased microcirculatory perfusion and not by mitochondrial respiratory or macrohemodynamic changes. Furthermore, the effect of STS on hepatic but not on intestinal microcirculation seems to be K(ATP)-channel-dependent.